Whole-body electromyostimulation and protein supplementation favorably affect sarcopenic obesity in community-dwelling older men at risk: the randomized controlled FranSO study - Kemmler W (Dove Medical Press, 2017)
Wolfgang Kemmler,1 Anja Weissenfels,1 Marc Teschler,1 Sebastian Willert,1 Michael Bebenek,1 Mahdieh Shojaa,1 Matthias Kohl,2 Ellen Freiberger,3 Cornel Sieber,3 Simon von Stengel1 1Institute of Medical Physics, Friedrich-Alexander University of Erlangen-Nürnberg, Erlangen, Germany; 2Faculty of Medical and Life Science, University of Furtwangen, Schwenningen, Germany; 3Institute of Biomedicine of Aging, Friedrich-Alexander University of Erlangen-Nürnberg, Nürnberg, Germany Background: Sarcopenic obesity (SO) is a geriatric syndrome characterized by the disproportion between the amount of lean mass and fat mass. Exercise decreases fat and maintains muscle mass; however, older people fail to exercise at doses sufficient to affect musculoskeletal and cardiometabolic risk factors. The aim of this study was to evaluate the effect of whole-body electromyostimulation (WB-EMS), a time-efficient, joint-friendly and highly individualized exercise technology, on sarcopenia and SO in older men. Materials and methods: A total of 100 community-dwelling northern Bavarian men aged ≥70 years with sarcopenia and obesity were randomly (1–1–1) assigned to either 16 weeks of 1) WB-EMS and protein supplementation (WB-EMS&P), 2) isolated protein supplementation or 3) nonintervention control. WB-EMS consisted of 1.5×20 min (85 Hz, 350 µs, 4 s of strain to 4 s of rest) applied with moderate-to-high intensity while moving. We further generated a daily protein intake of 1.7–1.8 g/kg/body mass per day. The primary study end point was Sarcopenia Z-Score, and the secondary study end points were body fat rate (%), skeletal muscle mass index (SMI) and handgrip strength. Results: Intention-to-treat analysis determined a significantly favorable effect of WB-EMS&P (P<0.001) and protein (P=0.007) vs control. Both groups significantly (P<0.001) lost body fat (WB-EMS&P: 2.1%; protein: 1.1%) and differed significantly (P≤0.004) from control (0.3%). Differences between WB-EMS&P and protein were significant for the Sarcopenia Z-Score (P=0.39) and borderline nonsignificant (P=0.051) for body fat. SMI increased significantly in both groups (P<0.001 and P=0.043) and decreased significantly in the control group (CG; P=0.033); differences between the verum groups and control were significant (P≤0.009). Handgrip strength increased in the WB-EMS group (1.90 kg; P<0.001; P=0.050 vs control) only. No adverse effects of WB-EMS or protein supplementation were recorded. Conclusion: WB-EMS&P is a safe and efficient method for tackling sarcopenia and SO in older men. However, the suboptimum effect on functional parameters should be addressed by increased voluntary activation during WB-EMS application. Keywords: sarcopenia, sarcopenic obesity, exercise, electrostimulation, older people